KAJIAN DAYA DUKUNG DAN DAYA TAMPUNG UNTUK KAWASAN PERMUKIMAN DI KABUPATEN BOLAANG MONGONDOW SELATAN - Nonto, Erlangga; Sela, Rieneke L. E.; Tinangon, Alvin J. (Department of Architecture, Engineering Faculty - Sam Ratulangi University, 2021)
The carrying capacity and capacity of land is an analytical instrument related to the limitations and needs of land in order to balance it, so that there is no land transfer and environmental damage. The residential area in South Bolaang Mongondow Regency is located on the river border and coastal area. Limited land due to hilly landscapes to steep slopes, no direction for the development of residential areas and the lack of community understanding regarding the carrying capacity and capacity of land are the main obstacles to the development of residential areas. Related to this, it is necessary to identify physical conditions and analyze the carrying capacity and capacity of existing land in 2020 until the prediction in 2040. The approach used is descriptive quantitative and spatial approach to determine physical conditions and analyze the projected carrying capacity and carrying capacity of land in 2020-2040. The results showed that South Bolaang Mongondow Regency had potential land with an area of 118,106 Ha. Posigadan District 23,606 Ha, Tomini 16,596 Ha, Helumo 13,475 Ha, Bolaang Uki 15,759 Ha, Pinolosian 16,533 Ha, Central Pinolosian 15,541 Ha, East Pinolosian 16,596. Based on the calculation of the land capacity of the most dominant sub-district that cannot accommodate the population in 2040, the Bolaang Uki District consists of 10 villages.